Prevention of Diabetes-Associated Cognitive Dysfunction Through Oral Administration of Lipopolysaccharide Derived From Pantoea agglomerans - Mizobuchi, Haruka; Yamamoto, Kazushi; Yamashita, Masashi; Nakata, Yoko; Inagawa, Hiroyuki; Kohchi, Chie; Soma, Gen-Ichiro (Frontiers in Immunology, 2021)
Diabetes-related cognitive dysfunction (DRCD) is a serious complication induced by diabetes. However, there are currently no specific remedies for DRCD. Here, we show that streptozotocin-induced DRCD can be prevented without causing side effects through oral administration of lipopolysaccharide (LPS) derived from Pantoea agglomerans. Oral administration of LPS (OAL) prevented the cerebral cortex atrophy and tau phosphorylation induced by DRCD. Moreover, we observed that neuroprotective transformation of microglia (brain tissue-resident macrophages) is important for preventing DRCD through OAL. These findings are contrary to the general recognition of LPS as an inflammatory agent when injected systemically. Furthermore, our results strongly suggest that OAL promotes membrane-bound colony stimulating factor 1 (CSF1) expression on peripheral leukocytes, which activates the CSF1 receptor on microglia, leading to their transformation to the neuroprotective phenotype. Taken together, the present study indicates that controlling innate immune modulation through the simple and safe strategy of OAL can be an innovative prophylaxis for intractable neurological diseases such as DRCD. In a sense, for modern people living in an LPS-depleted environment, OAL is like a time machine that returns microglia to the good old LPS-abundant era.